Dinamika pokazatel'ei serdechnogo ritma vo vremya vypolneniya stupenchato vozrastayushchei nagruzki na veloergometre u obsleduemykh s razlichnymi urovnyami fizicheskoi rabotosposobnoti - Dutov, V. S.; Severin, A. E.; Shatsun, S. A.; Shatsun, A. S. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of the research was to reveal the influence of the physical capacity's level on the cardiogram's indicies. Cardiac rhythm (R.M. Bayevsky), arterial pressure, electrocardiogram before the loading at the period of step by step increasing loading and at the 5-th minute of restoration had been registrated in 123 inspected persons. The obtained data had allowed to conclude: 1. The indicies of t he cardiogram can be used for the prognosis of the physical capacity's level together with traditionally used PWC170 test and other methods. 2. The decreasing of moda's amplitude and when moderate loading can be considered as a favourable prognostic criterion. 3. Index of the miocard's tension as an integrative characteristic of cardi-vascular system's activities can be also used for the control of the inspected person's functional state control.